Glycolysis inhibition via mTOR suppression is a key step in cardamonin-induced autophagy in SKOV3 cells - Daohua Shi; Di Zhao; Peiguang Niu; Yanting Zhu; Jintuo Zhou; Huajiao Chen (BMC, 2018)
Abstract Background Autophagy occurs in cells that undergoing nutrient deprivation. Glycolysis rapidly supplies energy for the proliferation of cancer cells. Cardamonin inhibits proliferation and enhances autophagy by mTORC1 suppression in ovarian cancer cells. Here, we investigate the relationship between cardamonin-triggered autophagy and glycolysis inhibition via mTORC1 suppression. Methods Treated with indicated compounds, ATP content and the activity of hexokinase (HK) and lactate dehydrogenase (LDH) were analyzed by the assay kits. Autophagy was detected by monodansylcadaverin (MDC) staining. The relationship between cardamonin-triggered autophagy and glycolysis inhibition via mTORC1 suppression was analyzed by Western blot. Results We found that cardamonin inhibited the lactate secretion, ATP production, and the activity of HK and LDH. The results demonstrated that cardamonin enhanced autophagy in SKOV3 cells, as indicated by acidic compartments accumulation, microtubule-associated protein 1 Light Chain 3-II (LC3-II) and lysosome associated membrane protein 1 up-regulation. Our results showed that the activation of mTORC1 signaling and the expression HK2 were reduced by cardamonin; whereas the phosphorylation of AMPK (AMP-activated protein kinase) was increased. We also confirmed that the AMPK inhibitor, Compound C, reversed cardamonin-induced upregulation of LC3-II. Conclusion These results suggest that cardamonin-induced autophagy is associated with inhibition on glycolysis by down-regulating the activity of mTORC1 in ovarian cancer cells.